Highly stretchable organic electrochemical transistors with strain-resistant performance - Chen, Jianhua; Huang, Wei; Zheng, Ding; Xie, Zhaoqian; Zhuang, Xinming; Zhao, Dan; Chen, Yao; Su, Ning; Chen, Hongming; Pankow, Robert M.; Gao, Zhan; Yu, Junsheng; et al. (Nature materials, 2022)
Realizing fully stretchable electronic materials is central to advancing new types of mechanically agile and skin-integrable optoelectronic device technologies. Here we demonstrate a materials design concept combining an organic semiconductor film with a honeycomb porous structure with biaxially prestretched platform that enables high-performance organic electrochemical transistors with a charge transport stability over 30–140% tensional strain, limited only by metal contact fatigue. The prestretched honeycomb semiconductor channel of donor–acceptor polymer poly(2,5-bis(2-octyldodecyl)-3,6-di(thiophen-2-yl)-2,5-diketo-pyrrolopyrrole-alt-2,5-bis(3-triethyleneglycoloxy-thiophen-2-yl) exhibits high ion uptake and completely stable electrochemical and mechanical properties over 1,500 redox cycles with 10 4 stretching cycles under 30% strain. Invariant electrocardiogram recording cycles and synapse responses under varying strains, along with mechanical finite element analysis, underscore that the present stretchable organic electrochemical transistor design strategy is suitable for diverse applications requiring stable signal output under deformation with low power dissipation and mechanical robustness. Highly stretchable organic electrochemical transistors with stable charge transport under severe tensional strains are demonstrated using a honeycomb semiconducting polymer morphology, thereby enabling controllable signal output for diverse stretchable bioelectronic applications.